Auto-correction of multiple spatial conflicts in multimedia authoring tools - Marvin Chandra Wijaya; Zulisman Maksom; Muhammad Haziq Lim Abdullah (Institute of Advanced Engineering and Science, 2023)
Multimedia authoring tool serves to facilitate an author to create multimedia presentations. Multimedia authoring tool will convert the multimedia presentation into a document. Mobile devices with different screen sizes that can cause visual media to overlap are called Spatio-temporal conflict. The process in the multimedia authoring tool involves a Spatio-temporal verification process to detect Spatio-temporal conflicts. This study proposes a method for correcting the conflict using a conflict region detection process, Spatio-temporal verification, and auto-correction. The auto-correction method uses two stages of area relocation for vertical conflict and horizontal conflict. The two stages are repeated for the ability to correct up to four conflicting regions. Visual media objects such as overlapping images and videos were successfully separated into non-overlapping media objects. The proposed method succeeded in separating the four media objects that were previously overlapping.